A technical note on the production of zirconia and zircon brick from locally available zircon in Bangladesh - Naher, Sumsun; Haseeb, A.S. Md. Abdul (Elsevier, 2006)
In this study, the potentiality of Bangladesh zircon as a raw material for zirconia and zircon brick production was examined. Decomposition of zircon (ZrSiO(4)) into zirconia (ZrO(2)) was attempted by using caustic soda (NaOH) as the decomposition agent. 5-10 mu m size zircon, 5-30 wt. NaOH, and decomposition temperatures ranging from 1300 to 1500 degrees C were investigated. X-ray diffraction method using Mo K alpha radiation was used in order to find out the extent of decomposition of zircon into zirconia. Zircon bricks of 0.06 mm x 0.06 mm x 0.025 mm shaped were made under a pressure of 15 MPa. Carboxi methyal cellulose (CMC) and Fe(2)O(3) were used as a binder. With increasing temperature and percentage of NaOH, decomposition of zircon increases. Crushing strengths and density of these bricks could be found as high as 53.36 MPa and 3210 kg/m(3), respectively. Bangladesh zircon can be used successfully for preparation of refractory bricks for high temperature use. (c) 2005 Elsevier B.V. All rights reserved.